In Memory of Raffaele Gianotti - Cesare Massone; Antonio Perasole (PAGEPress Publications, 2021)
Prof. Raffaele Gianotti ("Raf" for friends) was born on July 7th,1959 in Milan (Italy). His father, Prof. Ferdinando Gianotti (1920-1984), was a famous pediatric dermatologist that gave his name to the "papular acrodermatitis of childhood" (Gianotti-Crosti Syndrome) [...].